Tinjauan Runway Occupancy Time Landing Terhadap Konfigurasi Taxiway di Bandar Udara Haluoleo Kendari - Idyaningsih, Nining (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
The regularity of Air Traffic at Haluoleo Kendari Airport has not been fully fulfilled because it is proven that there are still frequent aircraft using the opposite runway must delay. conflict between aircraft and arrival aircraft in the condition where the aircraft will take off from runway 08 and landing runway 26. The purpose of the study was to determine the effect of each Flight Runway Occupancy Time landing on Haluoleo Kendari Airport. The method used is comparing the taxiway configuration and Runway Occupancy Time landing with ICAo Doc 9157 - Aerodome design manual part 2 taxiway, the balance between maximum capacity and efficiency of an aerodrome is located in the balance between runway and apron is taxiway as a link. The result is that ROTL aircraft that are operating too large and for flight efficiency must be reduced because they often prevent aircraft from taking off.